As condições de trabalho docente no atendimento educacional especializado na rede estadual de ensino público macapaense (2007-2020) - LAZAMÉ, Elioenai Silva (UNIFAP – Universidade Federal do Amapá, 2022)
The general objective of this research is to analyze the teaching work conditions in Specialized Educational Assistance (SEA) in public schools in Macapá city from 2009 to 2019. As theoretical-methodological fundamentals we adopt the dialectical historical materialism because we believe that the social phenomena in the bulge of a capitalist society are not explained in isolation but they are part of a historical totality. We adopted the bibliographic, documentary and field research. We selected three basic education goverment schools in Macapá. We interviewed 8 SEA professors who work in the Multifunctional Resource Room (MRR). For data interpretation, we opted for content analysis. The information obtained in the interviews and their dialogue with the theory was based on the categories of precariousness, intensification and versatility of the teaching work. The study is organized into three sections and introduction and final considerations. In the first section we present the discussions that deal with the category of working, teaching working conditions, considering the process of capital crisis, productive restructuring, counter-reform of the State and education. In the second section we present the particularities of Special Education in the Brazilian scenario and in the state of Amapá. We analyzed educational data regarding the number of enrollments, teachers, establishments and classes in special education in the period from 2007 to 2019. In the third section, we exposed the results of the survey. The results showed that the teachers of SEA who develop their work activities at MRR recognize that despite having the rooms of SEA, these rooms do not assist the specific needs of the public served adequately, either by the scarcity of technological and pedagogical materials, or by the lack of partitions and of the expanded physical space itself. The teachers unanimously expressed that to provide assistance to students with disabilities, they need to use their financial resources to purchase materials, print texts and activities, purchase educational games, in addition to using their own mobile internet data for the conducting school research. We also identified that teachers of special education characterize their work due to their versatility, due to the fact that they attend students with different disabilities, without taking into consideration the training, experience, the teacher's affinity in certain areas of specialized educational assistance and that this relationship of work is linked to the broader relations of the world of contemporary work.